Endogenous retrovirus EAV-HP linked to blue egg phenotype in Mapuche fowl - Wragg, David; Mwacharo, Joram M.; Alcalde, José A.; Wang, Chen; Han, Jian-Lin; Gongora, Jaime; Gourichon, David; Tixier-Boichard, Michèle; Hanotte, Olivier (Public Library of Science, 2013)
Oocyan or blue/green eggshell colour is an autosomal dominant trait found in native chickens (Mapuche fowl) of Chile and in some of their descendants in European and North American modern breeds. We report here the identification of an endogenous avian retroviral (EAV-HP) insertion in oocyan Mapuche fowl and European breeds. Sequencing data reveals 100% retroviral identity between the Mapuche and European insertions. Quantitative real-time PCR analysis of European oocyan chicken indicates over-expression of the SLCO1B3 gene (P<0.05) in the shell gland and oviduct. Predicted transcription factor binding sites in the long terminal repeats (LTR) indicate AhR/Ar, a modulator of oestrogen, as a possible promoter/enhancer leading to reproductive tissue-specific over-expression of the SLCO1B3 gene. Analysis of all jungle fowl species Gallus sp. supports the retroviral insertion to be a post-domestication event, while identical LTR sequences within domestic chickens are in agreement with a recent de novo mutation.